The parameters of Deschampsia antarctica population success comparative analyses in the region of Admiral bay (King-George island. The Inshore of Antarctica) - Parnikoza, I. Yu.; Ogeredova, I.; Miryuta, N.; Kozeretska, I. A.; Smykla, J.; Kunakh, V. A. (Ukrainian Antarctic Journal, 2013)
There are necessity (need) of vascular plant population success monitoring in Antarctica under warming condition. However, question about correlation between population success by different indices hasn’t been settled. The six Deschampsia antarctica populations have been investigated during the 2005/06 season in the region of Admiralti Bay (King-George Island) by series population success indices: individual cover or abundance, some biometric parameters and DNA relative content in nucleus of cell parenchyma foliage. Extremal grouping of quantitative comparison in pairs of these indices for studed D.antarctica populations has been to allow each compared pair locality to select groups with significant positive correlation between investigated indices and groups with significant negative correlation or central tendency to it. The population success in the case of positive correlation by part of indices have been determined to correlate to another part of its. In the case of negative correlation populations probability select strategy when increase in value of one parameter have been accompanied by decrease in value of another same. Populations with identical success by all investigated parameters have been selected to form specific clasters of complex population success. Monitoring of antarctic vascular plant population states (for example, D.antarctica) has been concluded to be conducted by as more as possible number of success parameters and to be estimated optimal conduction by search of correlation between every investigated parameters